The Importance of Mycological and Plant Herbaria in Tracking Plant Killers - Ristaino, Jean B. (Frontiers in Ecology and Evolution, 2020)
Mycological herbaria contain important records of plant biodiversity and past outbreaks of plant disease. Mycological herbaria have been used to: 1) understand the life history of plant pathogens; 2) identify outbreak strains and track their source; 3) understand the landscape ecology, biodiversity and distribution of native plants and their diseases and 4) examine the impact of climate change on pests and plant diseases. In this review, recent ecological and evolutionary questions being addressed using mycological herbarium specimens will be discussed followed by a case study on the evolution and migration of the historic outbreak strain of the Irish famine pathogen, Phytophthora infestans. Herbarium specimens are providing new information on the population biology and source of one of oldest plant diseases.